2011
DOI: 10.1016/j.ajpath.2011.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Oncostatin M as a STAT5-Dependent Mediator of Bone Marrow Remodeling in KIT D816V-Positive Systemic Mastocytosis

Abstract: Systemic mastocytosis is a neoplastic disease of mast cells harboring the activating KIT mutation D816V. In most patients, mast cell infiltration in the bone marrow is accompanied by marked microenvironment alterations, including increased angiogenesis, osteosclerosis, and sometimes fibrosis. Little is known about the mast cell-derived molecules contributing to these bone marrow alterations. We show here that neoplastic mast cells in patients with systemic mastocytosis express oncostatin M (OSM), a profibrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 49 publications
0
64
1
Order By: Relevance
“…The IL-6 family, including OSM, plays an anti-inflammatory role, and LIF, another member of the IL-6 family, also has antiinflammatory activity (22). Activation of STAT3 and STAT5 is associated with OSM expression (9,10). In this study, we found that OSM suppressed Th17 cell differentiation but induced Treg cell differentiation through the conversion of Treg into Th17 cells.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The IL-6 family, including OSM, plays an anti-inflammatory role, and LIF, another member of the IL-6 family, also has antiinflammatory activity (22). Activation of STAT3 and STAT5 is associated with OSM expression (9,10). In this study, we found that OSM suppressed Th17 cell differentiation but induced Treg cell differentiation through the conversion of Treg into Th17 cells.…”
Section: Discussionmentioning
confidence: 52%
“…It has recently been found to be involved in the expression of transcription factors associated with inflammatory and immune responses mediated by T cells (9,10). However, few studies have reported the effects of OSM on the proliferation of Th17 and Treg cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that OSM can maintain bone formation by means of OSM Receptor (OSMR) and STAT3, which acts on the recruitment, proliferation and osteogenic differentiation of mesenchymal progenitor cells (Guihard et al 2015). OSM can stimulate the growth of endothelial cells, fibroblasts and osteoblasts, which indicates that OSM may be a key regulator of the marrow microenvironment, which is helpful to the formation of bone (Hoermann et al 2011). These studies support our present finding that OSM has a potent stimulatory effect on the osteogenic differentiation of DPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Lentiviral transfection of HMC-1.2 cells with shRNA against FES was performed as described (45). A detailed description is provided in the Supplement.…”
Section: Knock-down Of Fes In Hmc-12 Cellsmentioning
confidence: 99%